Comparative analysis of body weight and serum biochemistry in broilers supplemented with some selected probiotics and antibiotic growth promoters - Haque, Md. Iqramul; Ahmad, Nazim; Miah, Mohammad Alam (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present work was conducted on Cobb-500 broilers fed with either probiotics (Yogurt, Promax®) or antibiotic growth promoters (Ciproflox®, Renamycin®) to assess the effects on body weight and biochemical parameters. Materials and methods: A total of 30 day-old broiler chicks were purchased and acclimatized for 7 days in the experimental shed. After initial acclimatization, the broilers were allotted into five equal groups (n=6). Group A was considered as control and was fed commercial ration and fresh drinking water. Groups B and C were fed commercial ration and probiotics (Yogurt, Promax®) respectively mixed in water. Groups D and E received commercial ration and antibiotic growth promoters (Ciproflox®, Renamycin®) respectively with water. Body weight of each bird was recorded on day 7, 14, 21, 28 and 35. At the end of trial period, the birds were sacrificed to collect blood in order to prepare serum samples for biochemical analyses considering total cholesterol, triglyceride, high density lipids (HDL), creatinine, alanine aminotransferase (ALT) and aspartate aminotransferase (AST). Results: Body weight in all treatment groups (B, C, D and E) was significantly (P<0.05) higher as compared to control (A) group. Total cholesterol and triglyceride levels significantly (P<0.05) decreased in probiotics treated groups as compared to control and antibiotic growth promoters treated groups. AST and ALT values increased significantly (P<0.05) in antibiotic growth promoters treated groups as compared to control whereas, these values decreased in probiotics treated groups. Creatinine levels were significantly (P<0.05) higher in antibiotic growth promoters treated groups as compared to all others groups. Conclusion: Significantly increased body weight is observed in probiotics and antibiotic growth promoters supplemented broilers. Probiotics also improve the lipid profile and other biochemical parameters as compared to growth promoter. Probiotics (like Yogurt and Promax®) seem to be better choice than antibiotic growth promoters as feed supplements. http://doi.org/10.5455/javar.2017.d226